COVID-19 and its impacts on health professionals active in the pandemic: A reflective theoretical study (Research, Society and Development, 2021)
In view of the COVID-19 virus, several preventive measures were necessary to avoid the contamination by the disease. WHO recommends the use of PPE, hand hygiene and social isolation, aiming to minimize contagion. For health professionals there is no possibility of isolation, as they are on the front line against COVID-19. The objective was to identify the damage caused to health professionals working on the front line against the COVID-19 Pandemic. This is a reflective theoretical study with a qualitative approach, built on the basis of critical reading of national and international references, existing in publications, about the damage caused to health professionals during the COVID-19 pandemic. The following databases were used: BVS and PubMed. 17 studies were selected, distributed nationally (76.47%) and internationally (23.53%). The results obtained evidenced nursing as a professional category that suffered the greatest impact, followed by medicine; there was a predominance of involvement in female professionals, aged between 40 - 50 years, of white race/color; the main symptoms related to their working hours and occupational exposure were: fear, insecurity, uncertainty, hopelessness, anxiety and depression. Therefore, assistance requires the implementation of strategies aimed at health professionals working on the front lines.